A Climatic Method,for Optimizing Cropping Patterns in Arid Kutch Region - Singh, R S; Ramakrishna, Y S (Annals of Arid Zone, 2016)
A climatic method is described for optimizing cropping patterns on the basis of mean length of the growing season as related to the distribution of annual rainfall. Application of the method for l3huj region in the Kutch district reveals that, for optimized and sustainable production, about 32% of the total agricultural land shoulb de covered by grasses or silvipastoral system compared to only 11% area under grasses at present. The method of optimizing the area allocation for the different crops that can provide sustainable production from a given farm area is also discussed.